Bony Cochlear Nerve Canal as a Predictor for Cochlear Nerve Status in Prelingually Deaf Children - Dokoska, Marija; Nikolova, Sonja; Kiteva Trenchevska, Gordana; Tilman, Keck; Netkovski, Jane (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/ Sciendo, 2023)
Objectives: The presence of a functional cochlear nerve is a key issue in the preoperative evaluation of pediatric candidates for cochlear implants. Correlations between cochlear nerve deficiency (CND) and bony abnormalities of the labyrinth or bony canal of the cochlear nerve are not yet well understood. The aim of this study was to determine whether the width of the bony cochlear canal (BCNC) can serve as a reliable predictive factor for the existence of a CND. Materials and methods: A total of 11 children with a confirmed diagnosis of prelingual, severe sensorineural hearing loss were included in this study. In all patients, indication for CI was confirmed and according to the preoperative protocol, high-resolution CT and MR were performed. Reconstructions at a distance of 0.6 mm of the axial plane and images from the HRCT of temporal bones were used for measuring the width of the BCNC. The cochlear nerves were evaluated on axial and sagittal - oblique T2 - MRI images and classified as normal, hypoplastic or aplastic. Two factors were reviewed retrospectively: the presence of inner ear anomalies and the relationship between BCNC stenosis and the existence of CND. Results: From a total of 22 temporal bones analyzed (22 ears in 11 patients), inner ear malformations were detected in 6 ears from 3 patients (27.27%). All three children had a bilateral malformation, in one it was Michel deformity and in two it was IP2 (incomplete partition 2). The BCNC diameter ranged from 0.1mm to 2.33mm with a mean value of 1.46±0.6mm. CND was recorded in 4 of 22 ears and all were associated with stenosis of the BCNC. In a total of three ears with a stenotic canal, we obtained a normal finding for the cochlear nerve on MR. Conclusion: Children with BCNC stenosis have a high incidence of CND. A narrowed BCNC on CT can be an indicator for the selection of children with sensorineural hearing loss who will need to be additionally referred for MRI in order to definitively assess the status of the cochlear nerve.
Keywords: bony cochlear nerve canal; profound sensorineural hearing loss; cochlear nerve; children